Broadband Low-Cost Microstrip Arrays for Water-Level Radar With Frequency-Stable Beams and Side-Sector Sidelobe Suppression - Kuang-Hsuan Huang; Yen-Sheng Chen (IEEE Access, 2025)
Water-level radar systems often rely on horn or lens antennas to achieve narrow-beam coverage and high gain, but scaling these designs for bistatic setups significantly increases size and installation complexity. This paper addresses these challenges by introducing a single-layer microstrip patch array, fabricated on a standard printed circuit board (PCB) substrate and fed by only uniform excitations, for bistatic water-level radar. The key novelty lies in systematically comparing two widely used feed architectures—series-fed and planar-fed—while demonstrating that the planar-fed structure not only avoids the beam steering observed in series-fed arrays but also achieves side-sector sidelobe suppression without complex amplitude tapers. A $16× 16$ planar-fed prototype demonstrates wide impedance and 3-dB gain bandwidths, near-constant beamwidth across its operational range, and suppressed side-sector sidelobes, marking a clear improvement over earlier microstrip arrays that rely on amplitude tapers or show frequency-dependent beam steering. These results confirm that uniform excitation is sufficient for maintaining broadside radiation and controlling sidelobes, offering a compact, broadband, and low-cost alternative to large horn assemblies. This work thus provides an effective solution that bridges theoretical array concepts and real-world radar deployment, meeting the stringent needs of water-level monitoring.